Educational Technology Resilience in Building Character in Elementary School Teacher Education Study Program in the 21st Century - Irfan Dahnial; Syamsuyurnita Syamsuyurnita (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The existence of the world of education cannot be separated from the word technology which leads to how education can survive well through technology in the world of education. One of the important agendas is how education can foster resilience to the swift currents of globalization which have an impact on every educator and student in the educational environment. Answering this challenge, the researcher focuses on strengthening character values that are continuously instilled in students so that students no longer do things that are contrary to the character values themselves. The problem in the world of education today is that there is still a drastic decline in character values in the elementary school environment which should not have happened. so in terms of education in the era of the 21st Century, it is necessary for prospective teachers in elementary schools to be prepared to answer challenges in the future. This research was conducted to reflect for readers how important education is for everyone who will live in the future with various kinds of challenges that will be faced later. Furthermore, in this study using a library research method by collecting previous research in outlining the results based on predetermined stages. The hope of this research is that with the resilience of educational technology in the 21st Century era, every educator is able to apply character, religious, social, and cultural values to each student according to the philosophy of the Indonesian nation.